Fluorine-doped carbon nitride quantum dots: Ethylene glycol-assisted synthesis, fluorescent properties, and their application for bacterial imaging. (November 2016) - Wang, Nan; Fan, Hai; Sun, Jianchao; Han, Zhenwei; Dong, Jing; Ai, Shiyun
Abstract: Fluorine-doped carbon nitride (FC3 N4 ) quantum dots were successfully synthesized on a large scale by a facile ethylene glycol-assisted ultrasonic method using bulk FC3 N4 powder as the precursor and ethylene glycol as the solvent. Characterization results show that high-quality FC3 N4 quantum dots with a uniform size of 1.5–2.0 nm were successfully prepared in ethylene glycol. Ethylene glycol is found to play an important role in the synthesis of quantum dots. Doping of fluorine in C3 N4 could adjust the band gap structure of C3 N4, resulting in altering the emission peak position and increasing the fluorescent intensity. The as-prepared FC3 N4 quantum dots in ethylene glycol show much higher fluorescent intensity with the quantum yield of 39.03%. The prepared FC3 N4 quantum dots were successfully applied as a fluorescent probe for bacterial imaging.